Successful Culture of Pelagia noctiluca (Cnidaria: Scyphozoa) Over Time: A Continuous Supply of the Holoplanktonic Jellyfish for Research and Industrial Applications - Ballesteros, Ainara; Páez, Diego; Santín, Andreu; García, Alba; Martín, Yeray; Alonso, Ester; Jourdan, Eric; Gili, Josep-Maria (Frontiers in Marine Science, 2022)
The scyphozoan Pelagia noctiluca has potential value for research and a wide variety of industrial applications. However, its holoplanktonic life cycle makes it difficult to maintain a permanent stock in aquaculture, unlike the continuous supply of newly-released ephyrae from jellyfish species with a benthic life stage. We investigated optimal feeding conditions for the captive breeding of P. noctiluca, monitoring total body diameter, morphological development, survival rate, and instantaneous growth rate. Diets of different items encapsulated in gelatin or non-motile prey were not suitable for successful growth of the early stages (ephyra and metaephyra), whereas rotifers were a sufficient food source for healthy growth. Fertilized eggs from sexually-mature jellyfish were obtained at 84.5 ± 2.1 and 87.0 ± 9.9 days post-fecundation in the presence and absence of gelatinous prey (Aurelia sp.), respectively. In contrast with the general consensus, we demonstrate that the incorporation of medusivorous prey was not essential for proper growth and closure of P. noctiluca life cycle. Instead, we recommend the inclusion of white shrimps (Acetes sp.) for the formation and maturation of gonads and production of eggs. Instantaneous growth rates (57.0% d-1), the highest reported to date for this species in captive conditions, were higher during the early stages. A third generation of cultured P. noctiluca was obtained for the first time (169 – 179 experimental days), demonstrating the durability of the culture, providing permanent stock and halving the production time of mature individuals compared to previous studies. Finally, we validated the use of captive-bred specimens through quantification of the hemolytic area after the sting process using the tentacle skin blood agarose assay methodology.